Features of creative burnout among educational workers in public administration system - Kryshtanovych, Myroslav; Akimova, Liudmyla; Akimov, Oleksandr; Parkhomenko-Kutsevil, Oksana; Omarov, Azad (Creativity Studies, 2022)
The purpose of the study is to form and determine the main ways to reduce creative burnout among employees of educational institutions. The object of the research is the employees of the educational service in Ukraine and their creative burnout. through the methods of analysis and synthesis of scientific and practical literature, we came to the conclusion that the following three methods should be used, as they will allow us to see which group of educators is estimated to have creative burnout. Due to the application of the IDEF0 methodology, the main ways to reduce their creative burnout have been identified. The reflected results received their practical application for the group of respondents in which, according to the assessment, a state of creative burnout was found. The value of this research lies in the systematization of existing methods for the formation of a certain methodological approach to assessing creative burnout and practical methods for reducing it. The results obtained showed that in a certain number of respondents, creative burnout decreased. The study has limitations and they relate primarily to the fact that, in addition to the methods we have chosen for assessing creative burnout, there are others that should be used in future research.